2019
DOI: 10.1186/s12862-019-1464-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced alphabet of prebiotic amino acids optimally encodes the conformational space of diverse extant protein folds

Abstract: Background There is wide agreement that only a subset of the twenty standard amino acids existed prebiotically in sufficient concentrations to form functional polypeptides. We ask how this subset, postulated as {A,D,E,G,I,L,P,S,T,V}, could have formed structures stable enough to found metabolic pathways. Inspired by alphabet reduction experiments, we undertook a computational analysis to measure the structural coding behavior of sequences simplified by reduced alphabets. We sought to discern chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…The structural and functional properties of early proteins are still debated. While previous studies have pointed out that acidic proteins can be soluble and sustain secondary structure information, it has generally been unclear how those proteins can form compact architectures and/or interact with the highly acidic nucleic acids (Doi et al 2011;Tanaka et al 2011;Longo et al 2013;Shibue et al 2018;Newton et al 2019;Solis 2019). A recent study by the Tawfik group suggested that polyamines and divalent cations may have played an important role in promoting the folding of such early proteins (Despotović et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The structural and functional properties of early proteins are still debated. While previous studies have pointed out that acidic proteins can be soluble and sustain secondary structure information, it has generally been unclear how those proteins can form compact architectures and/or interact with the highly acidic nucleic acids (Doi et al 2011;Tanaka et al 2011;Longo et al 2013;Shibue et al 2018;Newton et al 2019;Solis 2019). A recent study by the Tawfik group suggested that polyamines and divalent cations may have played an important role in promoting the folding of such early proteins (Despotović et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Even though different reduced sets (of 7–13) of the amino acid alphabet have been shown or predicted to be sufficient for protein folding and catalysis, to our knowledge, none of the experimental studies recovered enzyme activity in complete absence of aromatics 13–18 . Computational inquiry indicates that the aromatics are the strongest structure promoters among the 20 amino acid alphabet 19 .…”
Section: Introductionmentioning
confidence: 90%
“…Even though different reduced sets (of 7-13) of the amino acid alphabet have been shown or predicted to be sufficient for protein folding and catalysis, to our knowledge, none of the experimental studies recovered enzyme activity in complete absence of aromatics (13)(14)(15)(16)(17)(18). Computational inquiry indicates that the aromatics are the strongest structure promoters among the 20 amino acid alphabet (19).…”
Section: Introductionmentioning
confidence: 91%